Founder’s Syndrome: Starting (and Failing) a Spiritual Business in Sedona, Arizona - Crockford, Susannah (Implicit Religion, 2024)
Why would establishing a business resemble starting a religion? When group relations start to break down, why might it feel like a cult? This article examines the blurred lines between religion and business through a focus on the small-scale action of individuals trying to start something that has both economic and spiritual aspects but does not neatly fit into either category. Ethnographically situated in participant observation fieldwork in Sedona, Arizona in 2013, this article focuses on an individual kung fu practitioner and teacher trying to establish a school for martial arts. A close examination of the failure of this attempt, and how many of the students became alienated in the process, leads to an analysis of structural similarities between new religions and startups. In the US, social groups that exist in capitalism will inevitably have economic aspects; those that are also religious face a double bind of this reality with cultural norms derived from a Protestant separation of economics and religion. This article seeks an analytic route beyond this double bind through examining how the corporate form of spiritual seminars shares structural similarities with startups.